A descriptive physical analysis of water movement in the South West African Indian Ocean during the Northeast monsoon season - Lutjeharms, Johann R E (Department of Oceanography, 2016)
The Agulhas Current is unique as a western boundary current in having as its source of surface water currents that are linked to the variable current regions of the North Indian Ocean. In which way the Agulhas Current derives its supply from these currents and how these currents interrelate, is very poorly understood. In an attempt to make a contribution to the understanding of this flow an isentropic analysis in depth on seven σt-surfaces for the whole South West Indian Ocean during the Northeast Monsoon season was carried out. This analysis was augmented by the calculation of the velocities according to the Witte-Margules equation on each σt-surface at ten selected vertical sections. In addition the detailed volume transport and the velocity structure for each vertical section were calculated. The results pointed to a significant variation in transport and velocity structure from year to year. The large scale circulation in depth of the ocean is described. It is found that the Agulhas Current derives its supply of water from different sources at different depths and that at depth a large measure of recirculation of Agulhas Current Water takes place. It is not thought that this has been reported before and these findings might be of importance to the understanding of the current system as a whole. A few innovations in the standard oceanographic methods are described and two computer programs to aid analyses are presented.